(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The objectives of this research were to study the level of marketing mix factors and consumer behaviors of buying wine in Bangkok Metropolitan. The sample group was 330 People who used restaurant services at the Emerald Hotel, Charm Eatery Bar and Mazzaro Boutique Restaurant. The research instruments were a questionnaire and statistical applications used for data analysis were percentage, mean, t-test, F-Test (One-Way ANOVA) and Regression Analysis.The findings revealed that the most respondents were male, age between 36-45 years old, being private company employees and had average monthly income between 30,001-60,000 Baht. Overall level of marketing mix factors were the highest level of significance. Mainly behaviors found that the average drinking wine was 3 times a week, drinking wine along with their meal regularly, drinking wine in the evening, type of wine was red wine, type of taste was Dry, Image of wine was Smooth not astringent, the origin of wine from France Italy Germany Spain and the average cost of buying wine was 2,784 Baht. The results of hypothesis testing found that the sample group of different gender, age, career and average monthly income had different in consumer behaviors of buying wine in Bangkok Metropolitan, at a statistically significant at 0.05 level.